PERAN WARGA DALAM REVITALISASI SISKAMLING DI TENGAH PANDEMI COVID-19 SEBAGAI UPAYA MENJAGA KEAMANAN LINGKUNGAN - Khoirunisa, Nida (Saskara : Indonesian Journal of Society Studies, 2021)
Since the covid-19 pandemic, crime in the community has continued to increase. Kerep Village was appointed by the Kediri City Police Chief to run the Kampung Tangguh Program. In implementing the Kampung Tangguh program, Kerep Village strengthens environmental security by revitalizing the siskamling program that had been on a long halt. The purpose of this study was to analyze the role of the residents of Kerep Village RT 04 RW 03 in the revitalization of the Siskamling program using Max Weber's theory of social action. The method used in this research is descriptive qualitative method. The results showed that the role of Kerep Village residents in the revitalization of security systems in the midst of the Covid-19 pandemic included participating in deliberations on the establishment of environmental security posts, voluntary work for the establishment of environmental security posts, and night patrols.